Coopération des enseignants et nouvelles approches de l’organisation du travail dans les établissements scolaires - Laëtitia Progin Romanato; Monica Gather Thurler (Recherches en Éducation)
This contribution aims at highlighting the links between innovating forms of school work and the relationships existing between teachers who try to reach professional cooperation. We seek first to show that individualism is partly rooted in the forms of organization of school work closely related to the functioning of our systems. We then analyze the specificities and constraints involved in the implementation of a professional co-operation that we consider to be one of the conditions necessary for teachers to develop forms of school work better suited to the context of their institution. We finally conclude by presenting the "professional learning community" within which the practices of cooperation depend on five "pillars" which are at the results of the attempts that various actors undertake to develop the quality of teaching and learning.